Phase III, randomized study of ofatumumab versus physicians' choice of therapy and standard versus extended-length ofatumumab in patients with bulky fludarabine-refractory chronic lymphocytic leukemia. Issue 9 (1st September 2016) - Österborg, Anders; Udvardy, Miklós; Zaritskey, Andrey; Andersson, Per-Ola; Grosicki, Sebastian; Mazur, Grzegorz; Kaplan, Polina; Steurer, Michael; Schuh, Anna; Montillo, Marco; Kryachok, Iryna; Middeke, Jan Moritz; et al.
Abstract: We report results of a randomized, phase III study of ofatumumab versus physicians' choice treatment in patients with bulky fludarabine-refractory chronic lymphocytic leukemia and explore extended versus standard-length ofatumumab treatment. Patients (79 ofatumumab, 43 physicians' choice) completed a median 6 (ofatumumab) or 3 (physicians' choice) months' therapy. Ofatumumab-treated patients with stable disease or better were randomized (2:1) to 6 months' extended ofatumumab treatment or observation. Although the study did not meet the primary endpoint of progression-free survival (PFS) by independent review committee (ofatumumab: 5.4 months, physicians' choice: 3.6 months; p  =   0.27), median PFS by investigators was significantly longer for ofatumumab versus physicians' choice (7.0 versus 4.5 months; p  =   0.003) as was time to next therapy (median 11.5 versus 6.5 months; p  =   0.0004). PFS and time to next therapy were significantly longer with ofatumumab extended treatment than observation ( p  =   0.026 and p  =   0.002, respectively; n  =   37). The adverse-event profile of long-term ofatumumab administration showed no unexpected findings (Clinicaltrials.gov identifier: NCT01313689).